KERAGAMAN MAKROFAUNA TANAH PADA AGROFORESTRI JATI (Tectona grandis) DAN KIMPUL (Xanthosoma sangittifolium) - Aji Winara, S.Hut., M.Si. (Jurnal Agroforestri Indonesia, 2020)
Soil macrofauna has an important role in the ecosystems and soil fertility. Agroforestry patterns have environmental benefits such as providing living space for biodiversity including soil macrofauna. This study aims to measure the influence of teak and kimpul agroforestry on the diversity of soil macrofauna. The study was conducted on teak and kimpul agroforestry demonstration plots in the KPH Yogyakarta in January 2019. The research method used was monolith and hand sorting techniques and the analysis was carried out descriptively using the species diversity index approach. The results showed that teak and kimpul agroforestry patterns did not affect on the diversity of species and density of soil macrofauna. The level of diversity of soil macrofauna in teak and kimpul agroforestry, teak monoculture and kimpul monoculture are low. The value of soil macrofauna diversity in teak and kimpul agroforests is higher than teak monoculture and kimpul monoculture. A total of five types of soil macrofauna were found in 12-year teak agroforestry, six types in 42-year teak agroforestry, five types in 12-year teak monoculture, eight types in 42-year teak monoculture and five types in kimpul monoculture. The dominant soil macrofauna are Microtermes sp. and Anomala sp.